VOLUNTARY CONSUMPTION OF ETHYL OLEATE REDUCES FOOD INTAKE AND BODY WEIGHT IN RATS - Kemp, Christopher J. (2007)
Previous studies have shown that administration of the fatty acids, linoleic and oleic acid, either by intragastric or intraintestinal infusion, suppresses food intake and body weight in rats. While still not fully understood, gut-mediated satiety mechanisms likely are potential effectors of this robust response to gastrointestinal fatty acid infusions. The objective of this study was to assess the effects of voluntary access to an oleic acid derivative, ethyl oleate (EO), on subsequent food intake and body weight in rats. Animals were randomized either to a 12.5% EO diet or a soybean oil diet as a “breakfast,” followed either by two one-hour or one five-hour access periods to standard rodent diet, and food intake and body weights were collected. Across 14 days access, rats consuming EO on both feeding schedules gained less weight and consumed less total kilocalories than rats consuming the SO diet. Further, plasma levels of glucose and insulin were comparable in both EO and SO diet groups. In summary, EO was found to increase weight loss in rats maintained on a 75% food-restriction regimen, and attenuate weight-gain upon resumption of an ad-libitum feeding regimen. These data indicate that voluntary access to EO promoted short-term satiety, compared to SO diet, and that these effects contributed to a important and novel attenuated weight gain in EO-fed animals.